Experimental investigations influence of lengths barrel pistol on ballistic characteristics by use of long-term storage ammunition - Бірюков, Олексій Ігорович (Technology audit and production reserves, 2016)
Changes in physical properties of powder charges during their long-term storage have negative effect on the ballistic properties of 9 mm cartridges: the longer storage of ammunition – the greater the negative impact of this phenomenon. The paper presents a method of predicting the initial velocity of some cartridges based on the respective values of initial velocity of other pistols. The error of the predicted data ranged from 0,12 % to 1,98 % depending on the barrel length and ammunition storage period. It is proved that pistols with a longer barrel have larger deterioration in ballistic performance when used long-term storage ammunition than similar models with a shorter barrel. When comparing pistols PM, «FORT» and APS these deteriorations are 4 %, 4,84 % and 5,88 % respectively. The main reason for this factor using long-term storage ammunition is aging of powder charge. The consequence of this phenomenon is difficult to forecast change in the characteristics of the powder charge. This in turn reduces valuable work carried out by burning dust, and is the main driving force through which must be achieved performance inherent in the characteristics of weapons.